Serum 25 Hydroxyvitamin D Levels During Pregnancy in Women with Asthma: Associations with Maternal Characteristics and Adverse Maternal and Neonatal Outcomes - Jensen, Megan E. (Nutrients, 2020)
Low 25-hydroxyvitamin D (25(OH)D) levels are common in pregnancy and associated with adverse maternal/neonatal outcomes. In pregnant women with asthma, this study examined the association of lifestyle- and asthma-related factors on 25(OH)D levels and maternal/neonatal outcomes by vitamin D status. Serum 25(OH)D was measured at 16 and 35 weeks gestation in women with asthma (n = 103). Body mass index (BMI), gestational weight gain (GWG), smoking status, inhaled corticosteroid (ICS) use, asthma control, airway inflammation, and exacerbations, and maternal/neonatal outcomes were collected. Baseline and change (Δ) in 25(OH)D were modelled separately using backward stepwise regression, adjusted for season and ethnicity. Maternal/neonatal outcomes were compared between low (25(OH)D < 75 nmol/L at both time points) and high (≥75 nmol/L at one or both time points) vitamin D status. Fifty-six percent of women had low vitamin D status. Obesity was significantly associated with lower baseline 25(OH)D (Adj-R(2) = 0.126, p = 0.008); ICS and airway inflammation were not. Excess GWG and season of baseline sample collection were significantly associated with Δ25(OH)D (Adj-R(2) = 0.405, p < 0.0001); asthma-related variables were excluded (p > 0.2). Preeclampsia was more common in the low (8.6%) vs. high (0%) vitamin D group (p < 0.05). Obesity and excess GWG may be associated with gestational 25(OH)D levels, highlighting the importance of antenatal weight management.